Study on RuO2/CMK-3/CNTs composites for high power and high energy density supercapacitor. (1st September 2015) - Lo, An-Ya; Jheng, Yu; Huang, Tsao-Cheng; Tseng, Chuan-Ming
Highlights: CMK-3 integrated with RuO2 & CNTs greatly enhance the capacitance to 1102 F/g. The RuO2 /CMK-3/CNT ratio for supercapacitor electrode has been optimized. The power density (237 W/g) of RO10 /CMK67 /CNT23 is 3 folds of CMK-3. The energy density (0.15 W h/g) of RO10 /CMK67 /CNT23 is 4 folds of CMK-3. Abstract: In order to improve the energy density and power density of supercapacitors, the main concepts of this study are to exploit advantages of three different materials: high energy density of ruthenium oxides (RuO2 ), high power density of mesoporous carbon CMK-3, and high conductivity of carbon nanotubes (CNTs) to form a composite electrode. The crystallization and dispersion of RuO2, the effects of RuO2 mass fraction, and CMK-3/CNTs on energy/power densities are discussed. Microstructures of all the specimens are characterized by scanning electron microscopy (SEM), inductively coupled plasma-mass spectrometry (ICP-MS), transmission electron microscopy (TEM), N2 adsorption/desorption isotherm and X-ray diffraction (XRD) measurements. Furthermore, the specific capacitance and the ideal density of energy and power are derived from cyclic voltammetry (CV) method. In short, the combination of RuO2, CNT, and CMK-3 lead to enhanced the specific capacitance of 1102 F/g, energy density of 0.15 W h/g and power density of 237 W/g, which are 4 times and 3 times greater than those of CMK-3, respectively. The results provide effective routes to enhance the capacitance.